Online shopping cart & ordering system / Lee Siang Schee - Lee, Siang Schee (2002)
E-commerce (electronic commerce or EC) is the buying and selling of goods and services on the Internet, especially the World Wide Web, E-commerce makes purchasing easier for customer. However, it will cost a corporation a lot of money to build up a dynamic e-commerce website. To overcome this issue, a web-based E-commerce development tool is developed to create web page to selling the corporation's products. The proposed project offers a web-based service to let any shopping stores build their own web store from start to finish. It include template for online shopping cart, backend management and database. The dynamic database is hooked up to the existing back-end system for order fulfillment (storefront) and member registration process storefront). The aim of this project - Online hopping Cart and Ordering System (OSCOS) is to develop and design the e-commerce application for a shopping cart and ordering system. This project also defines the objectives, scope, problems and tools to use that should be identified before the development of this system. Several research and case study had done to do assessment and review about the system. Waterfall Model used as a methodology of the proposed project· Three-tier client/server architecture will be implemented to model the system architecture. In addition, Online Shopping Cart and Ordering System (OSCOS) is planned to be developed by using Personal Home Page (PHP) technology and Apache Web Server on the Window 98 platform utilizing database created using MySQL. The system design is dynamic and supporting concurrent user to interact with the system over Internet. Finally, the intended Online Shopping Cart and Ordering System (OSCOS) should able to produce the web pages that allow users to do online shopping and order the desired products. A database also has to be implemented for storing data that would be retrieved for display and captured from users.